Impact of chronic kidney diseases in feet health & quality of life: A case- series study. - Jiménez-Cebrián, Ana María; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Calvo-Lobo, César; Mazoteras-Pardo, Victoria; Morán-Cortés, Juan Francisco; Palomo-López, Patricia; López-López, Daniel (Elsevier, 2021)
Purpose The objective of this study is examine Quality of Life in subjects with chronic kidney disease utilizing Foot Health Status Questionnaire (FHSQ). Material and methods 101 subjects with chronic kidney disease (CKD) was studied in specialized clinics, in Extremadura (Spain). An observational descriptive study. The FHSQ was utilized to assess specific foot health (first section) and overall health (second division). The differences between clumps they were assessed using a t-test to independent samples. Results 59.40% (n = 60) were men and 40.59% (n = 41) women. The mean age was 68.77 ± 14.07. In first division of the FHSQ, a less score was registered in footwear domain (39.25) and in general foot health domain (46.37). In second division, less scores were resulted in general health domain (72) and vigour domain (60.43). CKD women got less scores in every domain. Women with CKD obtained significantly less scores in dimensions of foot pain, foot function, footwear, general foot health, general health and physical activity and there was no difference contrasted with men in the dimensions of social capacity and vigour. Conclusions The studied CKD population has problems their feet. Quality of life of CKD subjects is negatively impacted by health of their feet, difficulties with footwear, their overall health, and lack of vitality. Women with CKD show lower values of quality of life contrasted to male patients, associated with inability to perform physical activity, lack of energy and tiredness.
https://openpolicyfinder.jisc.ac.uk/id/publication/14144
Keywords: Pies - Enfermedades; Riñones - Enfermedades; Enfermos - Piscología; Pie; Enfermedades de pie; Enfermedades renales; Calidad de vida.; Pie; Enfermedades de pie; Enfermedades renales; Calidad de vida.; Pie; Enfermedades de pie; Enfermedades renales; Calidad de vida.; Pie; Enfermedades de pie; Enfermedades renales; Calidad de vida.